CONFLICT OF MARRIED WOMEN IN STORIES OF MANU BHANDARI: मन्नू भंडारी की कहानियों में विवाहित महिलाओं के संघष - Radhwani, Kukanta; Singh, Anita (International Journal of Research -GRANTHAALAYAH, 2018)
Manu Bhandari is a socialist writer of the post-independence era. His writings have the unique ability to catch macro and subtle changes coming in the society on the right surface. The effect of changes is always double - external and internal. One influence crushes a person from inside, and the other society gives equal support in making life hollow. The writer has raised the problems of married life on a double level, in her story she has depicted the subtle process of changing the relationship between the male-female traditional macro relationship. Manu Bhandari considers woman to be indispensable with the man in life, but she is not blind to her husband nor should she carry out the work of a housewife, only a machine. She also rivals her husband in political life to fulfill her principles, ideals and even marries or remarries when she feels alienated from her husband. Manu Bhandari creates various forms of woman in her story with full ease and seriousness to her modern woman, not as a woman draped by traditions, carrying the burden of slavery and slavery. मन्नू भंडारी स्वातंत्रोत्तर काल की समाजधर्मी लेखिका हैं। समाज में आने वाले स्थूल और सूक्ष्म परिवर्तनों को सही धरातल पर पकड़ने की अपूर्व क्षमता उनकी लेखनी में है। परिवर्तनों का प्रभाव सदा ही दोहरा होता है - बाह्य और आतंरिक। एक प्रभाव व्यक्ति को अंदर से कुरेदता है तो दूसरा समाज जीवन को खोखला बना देने में बराबर सहयोग पहुँचाता है। लेखिका ने दांपत्य-जीवन की समस्याओं को दोहरे स्तर पर उठाया है, उन्होंने अपनी कहानी में नारी-पुरुष परंपरागत स्थूल संबंध में बदलते संबंध की सूक्ष्म प्रक्रिया का चित्रण किया है। मन्नू भंडारी नारी जीवन में पुरुष के साथ को अनिवार्य मानती है लेकिन वह पति की अंधनुगामी नहीं है और न ही गृहिणी के दायित्व का निर्वाह करने वाली काम चलाऊ, मशीन मात्र। अपने सिद्धांतों, आदर्शों की पूर्ति के लिए वे राजनीतिक जीवन में भी पति की प्रतिद्वंदिता करती है और पति से अलगाव महसूस होने पर विवाह-विच्छेद या पुनर्विवाह भी करती है। मन्नू भंडारी अपनी कहानी में नारी के विविध स्वरूपों को रचकर उसके आधुनिक नारी को पूरी सहजता और संजीदगी के साथ उकेरती है, न की परंपराओं से दबी, कुचली और गुलामी का भार ढोती हुई नारी के रूप में।